Effectiveness of Sea Cucumber (Holothuria atra) Extract Ointment from the Talaud Islands on Burn Wound Healing in Mice (Mus musculus) - Mumu, Trivena Vannesa; Roring, Verawati Ida Yani; Manampiring, Nonny (Universitas Pattimura, 2026)
Sea cucumber (Holothuria atra) has been traditionally used for wound treatment; however, scientific evidence supporting its effectiveness in burn wound healing remains limited. This study presents a novel investigation of the wound healing potential of H. atra extract sourced specifically from the Talaud Islands and formulated into multiple topical ointment concentrations for second-degree burn treatment. The study aimed to evaluate the effectiveness of H. atra extract ointment in accelerating second degree burn wound healing in mice. The extract was obtained by maceration using 95% ethanol and formulated into ointments at concentrations of 10%, 15%, and 20%. Twenty-five male mice were randomly assigned to five groups: positive control (1% silver sulfadiazine), negative control, and three treatment groups receiving H. atra extract ointments at different concentrations. Parameters observed included wound diameter reduction, physical characteristics of the ointment, phytochemical screening, and pain-related behavioral responses. The results demonstrated that the 15% H. atra extract ointment produced the highest wound healing effectiveness, with a wound contraction rate of 96% on day 14, followed by the 10% (84%) and 20% (75%) formulations. Phytochemical analysis revealed the presence of flavonoids, saponins, steroids, and alkaloids, which are associated with anti-inflammatory, antimicrobial, and tissue regenerative activities. The ointment formulations met homogeneity and organoleptic requirements, although their spreadability values were below the recommended standard. These findings highlight the novelty of identifying an optimal concentration (15%) of H. atra extract ointment that provides superior burn wound healing activity compared with other tested concentrations. In conclusion, the 15% H. atra extract ointment shows potential as an alternative topical therapy for second-degree burn wounds.